1997
DOI: 10.1080/10400435.1997.10132305
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences of Frail Elders in Assistive Technology

Abstract: This study compared differences in coping strategies, such as the use and ownership of assistive devices and home modifications, for 64 black and 441 white frail elders from the University at Buffalo Consumer Assessment Study. Controlling age, income, and education, there was no difference between black and white elders on health and functional status. Black elders on average own and use fewer assistive devices than white elders. There is no difference between the two groups in the number of home modifications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 22 publications
1
23
0
1
Order By: Relevance
“…Black veterans used AT more than White veterans which was consistent with the predictions from the logistic regression analyses that indicated Black veterans were 1.3 times more likely to use AT compared to White veterans (OR = 1.30 CI: 1.20-1.42). The finding of Blacks using AT more than Whites was consistent with previous studies (Loggins et al, 2013); however, it contrasts some studies reporting higher use of assistive devices for Whites (Tomita et al, 1997).…”
Section: Discussionsupporting
confidence: 79%
“…Black veterans used AT more than White veterans which was consistent with the predictions from the logistic regression analyses that indicated Black veterans were 1.3 times more likely to use AT compared to White veterans (OR = 1.30 CI: 1.20-1.42). The finding of Blacks using AT more than Whites was consistent with previous studies (Loggins et al, 2013); however, it contrasts some studies reporting higher use of assistive devices for Whites (Tomita et al, 1997).…”
Section: Discussionsupporting
confidence: 79%
“…Most studies of wheelchair use consider wheelchairs as one category, i.e., a participant either does or does not use a wheeled mobility device [9][10][11]. The problem with these studies is that they assume all wheelchairs are created equal when, in fact, quite a range in cost, adjustability, and features exists.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers report that minorities and nonminority elders used comparable numbers of assistive devices (Tomita, Mann, Fraas, & Burns, 1997). In one study, elderly Blacks and Whites in western New York were reported to own and use comparable numbers of physical assistive devices.…”
mentioning
confidence: 98%